Factors influencing customer loyalty to internet service provider users of FirstMedia in Jakarta - Merdeysa Hadiatama (Indonesia Auditing Research Journal, 2021)
The purpose of this research is to find out what factors have a significant influence on customer loyalty in Internet Service Provider First Media users in Jakarta. For testing the validity from that hypothesis it's needed related data from Customer's opinion. Data explored based on one judgment and worker opinion from 185 respondents. The result of data analyze by Multiple Regression test shows that Ŷ = -2,336 + 0,066X1 + 0,149X2+ 0,047X3+ 0,030X4+ 0,390X5, Service Quality variable ( X1) t has calculated 3,516, Customer Satisfaction variable (X2) t calculate 2,480, Corporate Image variable (X3) t calculate 0.64, Price Perception variable (X4) t calculate 0.370, Switching Cost variable (X5) t calculate 5.449. By using a significant level of alpha (5%) hence all variables in this research are statistically significant. Coefficient of determination (adjusted R2) 0.563, this thing means that independent variables can explain about dependent variables equal to 56.3%. The F statistic test shows 48,486, it means that the independent variable influences customer loyalty in Internet Service Provider First Media users in Jakarta. Based on research by Multiple Regression test, it can be concluded that the variables of Service Quality, Customer Satisfaction, Corporate Image, Price Perception and Switching Cost influence both individually and simultaneously.